2007
DOI: 10.1097/01.csmr.0000306497.53648.d5
|View full text |Cite
|
Sign up to set email alerts
|

Genitourinary Problems in Bicyclists

Abstract: Genitourinary complaints are common in cyclists. Bicycle fit, improper saddle type, and individual anatomic factors are important evaluation criteria to consider when diagnosing symptoms and determining treatment options. By learning how to recognize and treat contributing factors, as well as learning a few simple bike-fitting techniques, physicians can treat and prevent many common problems associated with bicycling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…Bicycling has been linked to genitourinary problems (15, 16), including nerve entrapment syndromes (50–91% of cyclists), erectile dysfunction (13–24%), and other less common symptoms (priapism, penile thrombosis, hematuria, torsion of spermatic cord, perineal nodular induration, and prostatitis) (16). Two studies among long-distance competitive cyclists reported changes in semen parameters including a lower percentage of sperm with normal morphology (17), a higher proportion of morphologically abnormal tapered forms (17), and reduced sperm motility (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bicycling has been linked to genitourinary problems (15, 16), including nerve entrapment syndromes (50–91% of cyclists), erectile dysfunction (13–24%), and other less common symptoms (priapism, penile thrombosis, hematuria, torsion of spermatic cord, perineal nodular induration, and prostatitis) (16). Two studies among long-distance competitive cyclists reported changes in semen parameters including a lower percentage of sperm with normal morphology (17), a higher proportion of morphologically abnormal tapered forms (17), and reduced sperm motility (14).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, elevated scrotal temperature associated with certain types of exercise may cause atrophy of the testicular germinal epithelium and adversely affect spermatogenesis (4, 13, 14). Bicycle riding has been linked to several genitourinary problems (15, 16), and two studies among competitive cyclists reported changes in semen parameters including abnormal sperm morphology (17) and reduced sperm motility during periods of racing (14). …”
Section: Introductionmentioning
confidence: 99%
“…The nerve can be injured at any point along its course but is frequently compromised by the baby's head at the level of the ischial spine during the 2 nd stage of labour. The nerve is also vulnerable during cycling by pressure on the saddle on the sacrotuberous and sacrospinous ligaments and is referred to as "Cyclist Syndrome" [8].…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, the symptoms spontaneously resolved after 4 and 7 weeks [21]. Another study discussed various prevention strategies in order to prevent “genitourinary problems commonly associated with cycling,” including pudendal neuropathy, infertility, hematuria, testicular torsion, and testicular cancer [22], while a different case report in the literature described urethral strictures in two brothers who regularly engaged in BMX racing [23].…”
Section: Bicycle Riding and Sexual Dysfunction In Menmentioning
confidence: 99%